2022
DOI: 10.7554/elife.77663
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell RNA sequencing and lineage tracing confirm mesenchyme to epithelial transformation (MET) contributes to repair of the endometrium at menstruation

Abstract: The human endometrium experiences repetitive cycles of tissue wounding characterised by piecemeal shedding of the surface epithelium and rapid restoration of tissue homeostasis. In this study we used a mouse model of endometrial repair and three transgenic lines of mice to investigate whether epithelial cells that become incorporated into the newly formed luminal epithelium have their origins in one or more of the mesenchymal cell types present in the stromal compartment of the endometrium. Using scRNAseq we i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 52 publications
0
25
0
Order By: Relevance
“…Classical studies suggested that newly regenerated epithelia are mainly derived from proliferation of the remaining epithelia close to denuded stromal cells 55 . SSEA-1+ epithelial stem cells serve as a resident pool of progenitors for epithelial regeneration in uterus 6,16,37,54,56 . They have the potential to proliferate and restore epithelial integrity in case of cell death nearby 8 .…”
Section: Discussionmentioning
confidence: 99%
“…Classical studies suggested that newly regenerated epithelia are mainly derived from proliferation of the remaining epithelia close to denuded stromal cells 55 . SSEA-1+ epithelial stem cells serve as a resident pool of progenitors for epithelial regeneration in uterus 6,16,37,54,56 . They have the potential to proliferate and restore epithelial integrity in case of cell death nearby 8 .…”
Section: Discussionmentioning
confidence: 99%
“…[76] Studies have demonstrated that MET is crucial in the process of endometrial decidualization and plays a significant role in supporting embryonic development. [77,78] Furthermore, the activation of MET has been shown to counteract the development of uterine fibrosis in cases of IUA. [67,79] The MET process is known to occur during decidualization, [41,80] leading to the hypothesis that DSC-exos may encapsulate factors that promote MET and thus reverse the process of EMT in the injured uterus and inhibit excessive fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Next, to gauge the global relationship among major cell types, we projected the stromal, epithelial, and endothelial cells together, and observed a strong "flow" where stromal cells are upstream of both epithelial and endothelial cells (Figure 3F). This suggests that, unlike mice, human uterus stromal cells 14 have the potential to undergo a mesenchymal-to-epithelial transition to contribute to the epithelial and endothelial cell compartments during the normal menstrual cycle (22)(23)(24).…”
Section: Velocity Analysis Reveals Progenitors In Epithelium Endothel...mentioning
confidence: 99%
“…First, in hematopoietic stem-cell (HSC) transplant recipients (XX females receiving XY male HSC) bone marrow-derived human mesenchymal stem cells may contribute to uterine tissue homeostasis (3,6,20,21). Second, it was shown that perivascular or stromal cells in mouse myometrium may undergo a mesenchymal-to-epithelial transition (MET), playing a crucial role in the regeneration of epithelial cells in the uterus of mice after birth (22)(23)(24). While molecular markers for these stem/progenitor cells have been identified, our understanding of the cellular diversity in the uterus, especially the dynamics and interdependency of different cell types, remains limited.…”
Section: Introductionmentioning
confidence: 99%